Treatment of patients with hereditary angioedema with the c.988A>G (p.Lys330Glu) variant in the plasminogen gene - Konrad Bork; Karin Wulff; Guenther Witzke; Thomas Machnig; Jochen Hardt (Orphanet Journal of Rare Diseases, 2020)
Abstract Background Hereditary angioedema (HAE) in patients with normal C1 inhibitor (C1-INH) and the c.988A > G (p.Lys330Glu; p.K330E) variant in the plasminogen gene (HAE-PLG) is associated with skin swellings, abdominal pain attacks, and the risk of asphyxiation due to upper airway obstruction. Aim of this observational, retrospective study is to report about the efficacy of various treatments for acute attacks and long-term prophylaxis. Results The study included 111 patients with HAE-PLG. Thirteen patients were treated with icatibant for 201 acute swelling attacks. The mean duration of the treated attacks (mean 4.3 h; standard deviation [SD] 2.6 h) was significantly shorter than that of the previous 149 untreated attacks (mean 44.7 h; SD 28.6 h, p < 0.0001). Twelve patients were treated with plasma-derived C1-INH for 74 acute swelling attacks. The duration of the treated attacks (mean 31.5 h; SD 18.6 h) was significantly shorter than that of the previous 129 untreated in the same patients (mean 48.2 h; SD 32.5 h, p < 0.0001). Corticosteroids alone showed good response in 61/268 attacks (8 patients), low response in 82/268 attacks (7 patients), and no response in 125/268 attacks (26 patients). Corticosteroids combined with antihistamines showed good response in 13/309 attacks (4 patients), low response in 150/309 attacks (7 patients), and no response in 146/309 attacks (17 patients). Antihistamines alone were ineffective in all 37 attacks of 5 patients. In 2 patients with imminent asphyxiation due to tongue swelling and partial obstruction of the upper airways fresh frozen plasma was used without clinical response. The mean reduction in attack frequency was 46.3% under progestins (6 patients), 93.9% under tranexamic acid (3 patients) and 83.3% under danazol (3 patients). Conclusions For patients with HAE-PLG various treatment options are available, which completely or at least partially reduce attack duration or attack frequency.